The Pro-Soviet Message in Words and Images: Dyson Carter and Canadian “Friends” of the USSR - Anderson, Jennifer (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractDyson Carter, Sovietophile and member of the Communist Party of Canada, spent most of his career promoting the USSR to North Americans. He served as President of the Canadian-Soviet Friendship Society (CSFS) from 1949 to 1960, edited the CSFS newsletter News-Facts about the USSR from 1950 to 1956, and published the popular pro-Soviet magazine Northern Neighbors from 1956 until 1989. His work was supported from Moscow by the All-Union Society for Friendship with Foreign Countries (VOKS), and his writing had wide appeal on the Canadian left. Based on recently released archival material from Russia and Canada, as well as oral history, this story of propaganda and persuasion in Cold War Canada offers a new perspective on the history of the Canadian left.